Problems of Lighting in Modern Sewing Industries (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article provides information on the issues of natural and artificial lighting in the main production workshops of clothing enterprises, as well as provides valuable information about the problems of workshop lighting and their solutions.